An Experimental Analysis of the Use of Different Storage Technologies on a Relational DBMS - Praciano, Francisco D. B. S.; Abreu, Italo C.; Machado, Javam C. (Journal of Information and Data Management, 2020)
Traditional Database Management Systems (DBMSs) are built with the premise that magnetic disks such as hard disks drives (HDDs) store the data. Recently, several alternatives to HDDs have emerged, such as the solid-state drives (SSDs) based on non-volatile memory (NVM) technology such as 3D XPoint and the new generations of dynamic random access memories (DRAMs). Different characteristics of these storage technologies may impact the performance of DBMSs. In this work, we analyze the performance of a DBMS using three storage technologies as data locations:HDD, SSD NVM, and DRAM, as well as a hybrid way combining all three. To do this, we use two workloads, analytical and transactional, and we observe throughput as well as latency. After, we discuss the reasons for the results obtained for each type of storage. We also show that the query processing can benefit from the different characteristics of each storage technology to perform faster queries and, finally, we analyze the benefits of using a hybrid storage system.